Ketidakpastian Hukum Mengenai Batas Wajar Pembuatan Akta Dalam Peraturan Dewan Kehormatan Pusat Ikatan Notaris Indonesia Nomor 1 Tahun 2017 - Fendy Heryanto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
A notary is a public official appointed by the state through a minister whose duties are regulated in statutory regulations. Because a notary is a public official, those who serve as notaries must be able to maintain the honor and dignity of their position. Everything related to the duties of a Notary must be carried out in accordance with the Law on Notary Positions and the Notary's Code of Ethics. Authentic deeds as legal products from notaries are a form of certainty and legal protection for the parties concerned. Because it concerns legal certainty and legal protection for the community, that is the reason why Notaries in carrying out their official duties must comply with what has been regulated in the Notary Position Law and the Notary Code of Ethics. In making Deeds, Notaries in their Code of Ethics have regulated the reasonable limit of deeds that can be made in one day. However, this limitation does not provide certainty because it is also regulated in the same article that there is an exception that more than 20 deeds can still be made. The existence of regulations cannot provide certainty, which in fact must be regulated because the impact reaches the community. Therefore, this problem will become a question for Notaries and will also have an impact on legal certainty and protection for the public. It can be said to have an effect on society because legal products made by Notaries may one day lose their evidentiary power. Keyword: Notary; reasonable limits; Notarial Deed; Deed Making.